The Register Form of Pesantren Community in Semarang - Nafia, Fikriana; Rustono, Rustono (Pascasarjana Universitas Negeri Semarang, 2019)
The purpose of this study is to identify the form of the register used among pesantren community in Semarang. This research is a descriptive qualitative study.The data of this research are words, phrases, and acronyms that allegedly as register, while the data source is the speech of pesantren community in Semarang which contains registers. The data collection is done by using listen and talk method, through record technique.  Some forms of register pesantren community in Semarang are: (1) based on lingual units are, registers in the form of base words, words with affixes, compound words, and phrases, (2) based on the origin of the language are, register in Indonesian language, Javanese loanwords, Arabic loanwords, and Sundanese loanwords, (3) based on the register types, it is divided into open registers and closed registers.